Fantasy as a Peripheral Modernism: Uneven Development in Charles de Lint's Urban Fantasy - Matthew Rettino (2016)
Modern fantasy must be analyzed as a modernist literature that posits a critical gesture of refusal of the conditions of modernity. As a form of irrealism, a category that includes Gothic and magic realism, fantasy claims to represent a deeper realism even if it uses non-realist techniques to do so. The combined and uneven capitalist world-system inscribes itself in the urban fantasy of Charles de Lint, which as a peripheral modernism combines residual forms and folkloric, non-modern content within the realist novel. This symbolic act allegorizes 'the synchronicity of the non-synchronous, ' a principal condition of modernity. In de Lint's novel Moonheart, the uneven relationship between colonizer and colonized becomes symbolically resolved through its utopian romance structure, despite the incapability of the Canadian state's policy of multiculturalism to redress First Nations inequality. Mulengro expands the Gothic horror of a Rom superstition into a diagnosis of the general conditions of alienation that haunt modern capitalist society. In Dreams Underfoot, de Lint's short story collection, fantasy represents the unevenness of cities, where the right to the urban life is at stake within the sublime urban totality.